Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(1284-16401:231+58\) x\(11=1284-71+638\)
\(=1851\)
b)\(\frac{7}{4}+1\frac{1}{2}\)x \(1\frac{3}{2}:\frac{1}{4}=\frac{7}{4}+15\)
\(=\frac{67}{4}\)
c)\(2\frac{1}{4}+1\frac{2}{5}+\frac{4}{20}\)\(=\frac{9}{4}+\frac{7}{5}+\frac{1}{5}\)
\(=\frac{77}{20}\)
d)\(\left(\frac{12}{5}+\frac{2}{3}-\frac{11}{4}\right):\frac{3}{4}=\frac{19}{60}:\frac{3}{4}\)
\(=\frac{19}{60}\)x \(\frac{4}{3}\)
\(=\frac{19}{45}\)
a, 6/9+5/7+1/3=2/3+5/7+1/3=5/7+1=12/7
b, 17/7+6/5-20/14=17/7+6/5-10/7=6/5+1=11/5
c,2/5x1/4+3/4x2/5=2/5x(1/4+3/4)=2/5x1=2/5
d, 6/11:4/6+5/11:2/3=6/11:2/3+5/11:2/3=(6/11+5/11):2/3=3/2
nha
Ta có ; \(\frac{3}{7}\times\frac{4}{11}+\frac{3}{7}\times\frac{5}{11}+\frac{1}{2}\)
\(=\frac{3}{7}\times\left(\frac{4}{11}+\frac{5}{11}\right)+\frac{1}{2}\)
\(=\frac{3}{7}\times\frac{9}{11}+\frac{1}{2}\)
\(=\frac{27}{77}+\frac{1}{2}\)
\(=\frac{131}{154}\)
C1 : \(\frac{7}{11}\):\(\frac{3}{5}\)+\(\frac{4}{11}\):\(\frac{3}{5}\)
=\(\frac{7}{11}\)x\(\frac{5}{3}\)+\(\frac{4}{11}\)x\(\frac{5}{3}\)
=\(\frac{35}{33}\)+\(\frac{20}{33}\)
=\(\frac{55}{33}\)=\(\frac{5}{3}\)
C2: \(\frac{7}{11}\):\(\frac{3}{5}\)+\(\frac{4}{11}\):\(\frac{3}{5}\)
= \(\frac{3}{5}\)x (\(\frac{7}{11}\)+\(\frac{4}{11}\))
=\(\frac{3}{5}\)x 1= \(\frac{3}{5}\)
\(C1:\frac{7}{11}:\frac{3}{5}+\frac{4}{11}:\frac{3}{5}\)
\(=\frac{7}{11}x\frac{5}{3}+\frac{4}{11}x\frac{5}{3}\)
\(=\frac{35}{33}+\frac{20}{33}\)
\(=\frac{55}{33}=\frac{5}{3}\)
\(C2:\frac{7}{11}:\frac{3}{5}+\frac{4}{11}:\frac{3}{5}\)
\(=\frac{7}{11}x\frac{5}{3}+\frac{4}{11}x\frac{5}{3}\)
\(=\frac{5}{3}x\left(\frac{7}{11}+\frac{4}{11}\right)\)
\(=\frac{5}{3}x1=\frac{5}{3}\)
\(G=\frac{1}{1.2}+\frac{2}{2.4}+\frac{3}{4.7}+\frac{4}{7.11}+\frac{5}{11.16}\)
\(G=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{16}\)
\(G=1-\frac{1}{16}\)
\(G=\frac{15}{16}\)
\(G=\frac{1}{1.2}+\frac{2}{2.4}+\frac{3}{4.7}+\frac{4}{7.11}+\frac{5}{11.16}\)
\(G=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{16}\)
\(G=1-\frac{1}{16}\)
\(G=\frac{15}{16}\)
7/11+3/4+4/11+1/4
=7/11+4/11+3/4+1/4
=1+1
=2
\(\frac{7}{11}+\frac{3}{4}+\frac{4}{11}+\frac{1}{4}\)
= \(\left(\frac{7}{11}+\frac{4}{11}\right)+\left(\frac{3}{4}+\frac{1}{4}\right)\)
= \(\frac{11}{11}+\frac{4}{4}\)
= 1 + 1
= 2